The relationship between pain, analgesics and survival in patients with advanced cancer: a secondary data analysis of the international European palliative care cancer symptom study. - Boland, Jason W.; Allgar, Victoria; Boland, Elaine G.; Bennett, Mike I.; Kaasa, Stein; Hjermstad, Marianne Jensen; Johnson, Miriam (European Journal of Clinical Pharmacology, 2020)
© 2019, The Author(s). Purpose: Opioids reduce cancer-related pain but an association with shorter survival is variably reported. Aim: To investigate the relationship between pain, analgesics, cancer and survival within the European Palliative Care Cancer Symptom (EPCCS) study to help inform clinical decision making. Methods: Secondary analysis of the international prospective, longitudinal EPCCS study which included 1739 adults with advanced, incurable cancer receiving palliative care. In this secondary analysis, for all participants with date of death or last follow up, a multilevel Weibull survival analysis examined whether pain, analgesics, and other relevant variables are associated with time to death. Results: Date of death or last follow-up was available for 1404 patients (mean age 65.7 [SD:12.3];men 50%). Secondary analysis of this group showed the mean survival from baseline was 46.5 (SD:1.5) weeks (95% CI:43.6–49.3). Pain was reported by 76%; 60% were taking opioids, 51% non-opioid analgesics and 24% co-analgesics. Opioid-use was associated with decreased survival in the multivariable model (HR = 1.59 (95% CI:1.38–1.84), p< 0.001). An exploratory subgroup analysis of those with C-reactive protein (CRP) measures (n= 219) indicated higher CRP was associated with poorer survival (p= 0.001). In this model, the strength of relationship between survival and opioid-use weakened (p= 0.029). Conclusion: Opioid-use and survival were associated; this relationship weakened in a small sensitivity-testing subgroup analysis adjusting for CRP. Thus, the observed relationship between survival and opioid-use may partly be due to tumour-related inflammation. Larger studies, measuring disease activity, are needed to confirm this finding to more accurately judge the benefits and risks of opioids in advanced progressive disease.
Keywords: Neoplasms; Pain; Analgesics; Opioids; Survival